The Overreliance on Portable Classrooms in Ontario Schools: New Evidence for the Study of Austerity and Disinvestment in Canadian Public Education - Riveros, Augusto (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2023)
This study investigates the extent of portable classroom use in the province of Ontario between the years 2010 and 2020. The research uses administrative data obtained from the Ontario Ministry of Education and from the 27 largest school boards in the province. The findings reveal that portable classrooms are used as long-term solutions to address enrolment pressures in schools, which is symptomatic of the austerity-driven policies in the funding of Ontario’s public education. In addition to providing new evidence of the effects of funding cuts in education, this study repositions infrastructure planning as a critical concern for education policy research.